MOOREN’S ULCER - Lylys Surjani (Universitas Methodist Indonesia, 2020)
Mooren's ulcer is chronic ulcerative keratitis that is generally painful, progressive starting peripherally and progressing in a circular and centralized manner, either unilateral or bilateral without scleritis and without systemic disease. Mooren's ulcer mostly idiopathic. Mooren's ulcer was divided into three type which is unilateral, bilateral progressive and bilateral indolent. Initial treatment for Mooren's ulcer consists of topical corticosteroids. If corticosteroids do not control inflammation, excision of the limbal conjunctiva can be performed. This case report describes the diagnosis and management of a case of mooren's ulcer without an obvious cause. This topic is important to discuss and requires prompt and adequate management because one of the complications is perforation which can lead to blindness.